Isolated Persistent Left Superior Vena Cava, Role of Echocardiography Screening and CT angiography - Putrika Prastutu Ratna Gharini; Erika Maharani; Lucia Kris Dinarti (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2016)
Background: An isolated persistent left SVC with concomittant agenesis of right SVC in adult patients is a very rare abnormality. Physician should consider it particularly in patients, in which venous acces will be performed. Our rare case deals with the importance of detailed echocardiographic examination with screening of coronary sinus dilatation before the electrophysiology study.Case: A 65-year-old woman came to outpatient clinic for a chief complaint of palpitations. Her ECG showed paroxysmal SVT with WPW syndrome. She underwent echocardiography examination before electrophysiology study and it was found that she had a dilated coronary sinus. Therefore we performed cardiac CT. It was found that she had a persistent left superior vena cava (SVC) and an absence of a right SVC with no other congenital anomaly.Conclusion: A comprehensive echocardiography examination to look for a dilation of coronary sinus is a first suggestion to screen this anomaly, eventually followed by echocardiography with agitated saline injection and/or computed tomography can help physician to anticipate the anomaly before the invasive procedure involving the thoracic vein.Keywords: echocardiography, cardiac CT angiography, vascular malformation, superiorvena cava